ANALISIS NILAI KEBUDAYAAN DAN UNSUR KEBAHASAAN DALAM PUJIAN â€œSEMBAHYANGâ€ - Hardiana, Maulidia Tifani Alfin Nur (Hasta Wiyata, 2021)
This study aims to 1) analyze the value of culture; and 2) analyze linguistic elements in praise of "Sembahyang". The method used in this research is the literature and literature hermeneutic method. The object of this study is a compliment entitled "Sembahyang" which is analyzed based on cultural values and linguistic elements. Based on the analysis, it can be concluded that the cultural values to be conveyed in this praise that all people have the same position in the eyes of God. God will not look at the economic conditions, classes, social strata, and physical conditions of his people. Therefore, as a people of creation God basically has the same obligation towards God. The linguistic element in the praise lyrics uses a lot of inversion sentences, namely the existence of a predicate precedes the subject.